Quantitative assessment of flood discharges and floodway failures through cross-cultivation of advancement in knowledge and traditional practices. Issue 4 (16th November 2018) - Wahalathantri, Buddhi; Lokuge, Weena; Karunasena, Warna; Setunge, Sujeeva
Abstract : Purpose: The 2011 and 2013 Queensland, Australia flood events caused massive infrastructure damage for low-level stream crossings such as floodways and culverts in regional Queensland. Failures of newly built floodways during the 2013 Queensland flood event in the Lockyer Valley Regional Council area raised significant concerns with respect to floodway design practices adopted in Australia and attracted significant research interest to enhance the resilience of floodways. Review of existing floodway design guidelines indicates that floodway design process is closely related to hydraulic and hydrological aspects. However, conducting a hydrological analysis is a challenging in rural areas, mainly owing to information scarcity. Floodways in rural areas often require a simple and economical solution contrast to more detailed hydrological analysis approaches adopted in urbanised areas. This paper aims to identify and apply the rational method to estimate maximum flood discharges at selected floodway locations in the Lockyer Valley Regional Council area. The paper further attempts to provide the first insight of flood characteristics during the 2011 and 2013 Queensland flood events at three catchment outputs across the selected case study area. It also highlights modern day challenges for practising engineers and researchers when estimating flood characteristics in rural areas. The paper shows that cross-cultivation of advancement in engineering practices and traditional approaches can promote quantitative approaches when assessing floodway damage in regional areas. Design/methodology/approach: The research identifies limitations when assessing flood impact in rural regions in collaboration with experience from industry partners and authors themselves. The authors developed a framework to overcome those limitations arising from information scarcity to minimise the trial and error design approaches utilised in the current design practices for floodways. Findings: This paper developed a simple and effective hydrological method with minimum inputs. It also provides an example on collating available but scattered resources and traditional method to quantitatively assess flood discharges of a rural catchment in Australia. Flood discharges at three catchment outlets along the Left-Hand Branch Road in the Lockyer Valley Region during both 2011 and 2013 Queensland flood events are estimated for the first time. The findings highlight the impact of flood discharges and flooded period on floodway failures. Research limitations/implications: The current research is based on a selected case study area in Australia. However, similar challenges are expected all across the world, due to the scarcity of rainfall and flood measurement gauges. Practical implications: Floodway designers can apply similar framework to estimate the flood discharges instead of current practice of trial and error process. This will provide more scientific and reliable estimation and assessment process. Social implications: One of the social impacts identified in the broader research is the community outrages and disagreement between floodway design engineers and the community. Following the developed framework in the manuscript, design engineers will be able to justify their assumptions and design work. Originality/value: The paper presents a novel framework on collating different and scattered information towards estimating flood discharges in rural areas. The manuscript presents the first insights on estimated flood discharges in the selected case study area during the 2011 and 2013 Queensland flood events. This will enable further research to be performed in a quantitative manner rather than the present approach of qualitative manner.